Problematics in the Use of Learning Media in Grade 1 SDN 13 Lolong Belanti - Efrina, Gusnita; Rahmi, Felly Lailatul; Wati, Wikke Widya (TOFEDU: The Future of Education Journal, 2023)
This observation was carried out to find out the problems and use of learning media in Elementary School 13 Lolong Belanti. This observation uses a qualitative method. Elementary schools used in this observation include SDN 13 lolong belanti. From the data collected by observation techniques, interviews, and documentation using observation sheets and interview guides. The results of this observation indicate that the learning media problem in elementary school SDN 13 lolong belanti is that learning media are not yet available in the independent curriculum, there is no storage space so that the media is damaged, lost and not maintained, and the teacher's insights are limited in using the media. The use of media in the Lolong Belanti elementary school has not been maximized due to the availability of media in each school. In general, the use of media by teachers at SDN 13 lolong belanti is the use of media en masse or in groups in front of the class. Some teachers have used environmental media and used materials in learning.